2008
DOI: 10.1186/1742-4690-5-107
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic decay kinetics suggest progressive slowing in turnover of latently HIV-1 infected cells during antiretroviral therapy

Abstract: Background: Mathematical models based on kinetics of HIV-1 plasma viremia after initiation of combination antiretroviral therapy (cART) inferred HIV-infected cells to decay exponentially with constant rates correlated to their strength of virus production. To further define in vivo decay kinetics of HIV-1 infected cells experimentally, we assessed infected cell-classes of distinct viral transcriptional activity in peripheral blood mononuclear cells (PBMC) of five patients during 1 year after initiation of cART

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
69
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 51 publications
(95 reference statements)
15
69
2
Order By: Relevance
“…The model assumes a heterogeneous population of latently and persistently infected cells having occasional transcriptional bursts to increase their level of RNA transcription which is consistent with experimental data from Fischer et al [12].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The model assumes a heterogeneous population of latently and persistently infected cells having occasional transcriptional bursts to increase their level of RNA transcription which is consistent with experimental data from Fischer et al [12].…”
Section: Discussionsupporting
confidence: 75%
“…It is important to note, however, that the characteristic decay profile in the study by Fischer et al [12] could also be a result of differential trafficking of virus particles and HIV-1-infected subpopulations of cells between the blood and lymphoid tissue. Furthermore, it has also been suggested that the virion clearance rate from the blood corresponds to a virion efflux to other organs where the virus is ultimately However, we have excluded this effect for simplicity.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 94%
See 3 more Smart Citations